АВСТРАЛИЯ МАТЕРИГИН ОҚЫТЫЎДА ИНТЕРАКТИВ МЕТОДЛАРДАН ПАЙДАЛАНЫЎ УСЫЛЛАРЫ - Жиемуратова, Г. (ILIM hám JÁMIYET, 2019)
The article is devoted to research the methods of teaching the continent Australia with the help of such techniques of the interactive method as “Cluster”, “Geographical dictation” and “Venn diagram” that promote to improve pupils’ skills like working individually, to analyze and compare.